THE FIRST RUSSIAN EXPERIENCE OF ABO-INCOMPATIBLE KIDNEY TRANSPLANTATION WITH ANTIGEN-SPECIFIC IMMUNOADSORPTION - Y. G. Moysyuk; A. I. Sushkov; N. V. Pulkova; V. Y. Abramov; A. G. Kupriyanova; B. N. Morozov; A. K. Porunova; N. P. Obraztsova; I. Y. Adamova; S. V. Gautier (Вестник трансплантологии и искусственных органов)
We report the first Russian experience of successful ABO-incompatible kidney transplantation using anti-CD20 + IA + IvIg pretransplant conditioning protocol and tacrolimus + MMF + steroids as maintenance immunosuppression. IA procedures were performed on reusable columns ABO-Adsopak® (POCARD Ltd. Moscow, Russia). IA treatments following the administration of rituximab efficiently lowered the immunoglobulin M (IgM) and G (IgG) anti-A/B antibodies titers in all patients. The transplantation could be performed in all cases and the kidneys showed primary function. Unfortunately, the biopsy-proven clinical antibody-mediated rejection (AMR) occurred in one case. Episo- de of AMR was successfully reversed. On 6, 4 and 2 months follow-up, serum creatinine levels were 117, 127 and 87 μmol/l, respectively. We consider ABO-incompatible transplantation as a safe and promising procedure in particu- lar cases for those patients having related but ABO-incompatible donors. Given the shortage of donor organs ABO- incompatible living donor kidney transplantation may become a treatment of choice for many patients.